A case of incorrect evaluation of intestinal patency by early dissolution of a patency capsule - Teppei Omori; Toshifumi Hara; Shun Murasugi; Harutaka Kambayashi; Yu Sasaki; Miki Koroku; Maria Yonezawa; Keiichi Morishita; Shinichi Nakamura; Katsutoshi Tokushige (DEN Open)
Abstract A 60‐year‐old man presented with a suspected small intestinal tumor on positron‐emission tomography‐computed tomography. Small bowel capsule endoscopy (SBCE) was planned for close examination of the small intestine. To avoid retention of the SBCE due to strictures, a patency capsule (PC) was first used to evaluate patency. However, PC discharge was not visually confirmed during the 24‐h period. No obvious PC was observed on plain abdominal radiography performed in the standing position. The patient underwent SBCE, assuming that the PC had been shed inconspicuously. SBCE revealed a neoplastic lesion with stenosis at a site thought to be the upper small intestine and remained stagnant at the same site for the duration of the battery. In addition, in the SBCE image, a PC shell was captured in the intestinal tract on the oral side of the stenosis. When the pre‐SBCE plain abdominal radiograph was enlarged to confirm the details, PC was observed in the lateral and decubitus views as a dissolved shell only. To the best of our knowledge, no previous report has described the complete dissolution of a PC leaving only its shell during a 30‐hour patency evaluation period. This case illustrates that, in the absence of visual confirmation of a PC discharge, PC may have remained in the body due to premature dissolution. Additional examinations or plain X‐ray imaging should be performed to confirm this, with no preconceived notions that the PC will not dissolve within 30 hours of administration.